2020
DOI: 10.1101/2020.01.20.912634
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

RADX Sustains POT1 Function at Telomeres to Counteract RAD51 Binding, which Triggers Telomere Fragility

Abstract: The 3' terminal DNA extensions at chromosome ends can become engaged into multiple biochemical reactions during DNA replication, telomerase-mediated telomere extension, homology directed DNA repair, nucleolytic processing and DNA damage checkpoint activation. To keep these activities in check, telomeric 3' overhangs can be hidden in t-loop structures or they associate with specialized proteins such as POT1. Here, we explore the telomeric microenvironment using a proximity-dependent labeling approach and identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…These studies suggest that RADX antagonizes RAD51 at replication forks to balance fork remodeling and stabilization to maintain genome stability ( 17 ). Intriguingly, a recent study also showed that RADX is involved in telomere protection ( 19 ). RADX binds exposed single-stranded telomeric DNA along with POT1 to antagonize the accumulation of RAD51 and reduce sister telomere associations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies suggest that RADX antagonizes RAD51 at replication forks to balance fork remodeling and stabilization to maintain genome stability ( 17 ). Intriguingly, a recent study also showed that RADX is involved in telomere protection ( 19 ). RADX binds exposed single-stranded telomeric DNA along with POT1 to antagonize the accumulation of RAD51 and reduce sister telomere associations.…”
Section: Discussionmentioning
confidence: 99%
“…RADX-depleted cells exhibit excessive RAD51 activity and illegitimate recombination, suggesting that RADX is a negative regulator of RAD51 that functions at replication forks to maintain genome stability ( 17 ). A recent study also showed that RADX is involved in telomere maintenance by binding single-stranded telomeric DNA along with POT1 to antagonize RAD51 ( 19 ). The mechanistic basis of how RADX acts on ssDNA to negatively regulate RAD51 is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…HEK 293E cl75 was generated by transfecting pSpCas9(BB)-2A-Puro (PX459) plasmid expressing gRNAs targeting the genomic region proximal to the start codon of TRF1 (TRF1-gRNA: 5’-GCGAGCCATTTAACATGGCGG-3’) or TRF2 (TRF2-gRNA: 5’-TCTATCATGGCCGCGGGAGC-3’) and non-linearized repair template plasmid 67 . The repair template contained 600bp homology region flanking both sites of the start codon of TRF1 or TRF2 amplified from genomic DNA of HEK293E cells, and combined with three tandemly repeated FLAG tags, EcoRI restriction site, Kozak sequence and linker base pairs by using overlapping PCR.…”
Section: Methods Detailsmentioning
confidence: 99%
“…RADX binds exposed single telomeric DNA along with POT1 to antagonize the accum RAD51 and reduce sister telomere associations. Depletion RAD51 or BRCA2 at telomeres rescued RADX depletion, s that RADX also antagonizes homologous recombination in th (19).…”
Section: Discussionmentioning
confidence: 92%
“…Loss of RADX leads to excessive RAD51 activity replication forks, slowing elongation and causing fork collap studies suggest that RADX antagonizes RAD51 at replicatio balance fork remodeling and stabilization to maintain genom (17). Intriguingly, a recent study also showed that RADX is in telomere protection (19). RADX binds exposed single telomeric DNA along with POT1 to antagonize the accum RAD51 and reduce sister telomere associations.…”
Section: Discussionmentioning
confidence: 99%